Eco-Digital Citizenship: The New Frontier of Pancasila Anti-Corruption Education - Kadek Ayu Ariningsih; Soma Surya Persada; Krisnanda Theo Primaditya (Sidyanusa, 2026)
Anti-corruption education within Pancasila education has largely been framed as part of character education, emphasizing individual morality such as honesty, responsibility, and discipline. While this approach provides an important ethical foundation, it tends to reduce corruption to a matter of personal conduct and overlooks its broader structural and ecological consequences. This article addresses this limitation by examining how anti-corruption education can be reconsidered beyond an individual moral framework. Using a critical literature review, this study analyzes the intersections between anti-corruption education, Pancasila education, and environmental education. The analysis identifies a dominant tendency to frame corruption as a moral issue, alongside a conceptual disconnection between anti-corruption discourse and ecological concerns. At the same time, emerging perspectives in environmental ethics and civic education suggest the need to understand corruption in relation to its systemic and ecological impacts. Based on these findings, this article proposes a reframing of anti-corruption education through the lens of ecological responsibility. Rather than treating corruption solely as a moral violation, it is conceptualized as a relational phenomenon with broader social and environmental consequences. This perspective positions anti-corruption education as part of a civic-ecological framework that connects integrity with ecological awareness. By doing so, the study offers a conceptual direction for rethinking value-based education within Pancasila education in a way that is more responsive to contemporary challenges.